Brain endothelial cell junctions after cerebral hemorrhage: Changes, mechanisms and therapeutic targets. Issue 8 (August 2018) - Keep, Richard F; Andjelkovic, Anuska V; Xiang, Jianming; Stamatovic, Svetlana M; Antonetti, David A; Hua, Ya; Xi, Guohua
Vascular disruption is the underlying cause of cerebral hemorrhage, including intracerebral, subarachnoid and intraventricular hemorrhage. The disease etiology also involves cerebral hemorrhage-induced blood–brain barrier (BBB) disruption, which contributes an important component to brain injury after the initial cerebral hemorrhage. BBB loss drives vasogenic edema, allows leukocyte extravasation and may lead to the entry of potentially neurotoxic and vasoactive compounds into brain. This review summarizes current information on changes in brain endothelial junction proteins in response to cerebral hemorrhage (and clot-related factors), the mechanisms underlying junction modification and potential therapeutic targets to limit BBB disruption and, potentially, hemorrhage occurrence. It also addresses advances in the tools that are now available for assessing changes in junctions after cerebral hemorrhage and the potential importance of such junction changes. Recent studies suggest post-translational modification, conformational change and intracellular trafficking of junctional proteins may alter barrier properties. Understanding how cerebral hemorrhage alters BBB properties beyond changes in tight junction protein loss may provide important therapeutic insights to prevent BBB dysfunction and restore normal function.